Pendidikan Demokrasi Studi Relasi Komunikasi Politik terhadap Partisipasi Politik Menghadapi Pemilu - Arasid, Mohamad Ikrom; Wahyiah, Ita Rosita; Arifin, Suherman; Laksana, April; De Fretes, Safira Britantia; Pratiwi, Rida Astuti (Universitas Islam Negeri Imam Bonjol Padang, 2023)
The case of not achieving the amount of community participation in the 2020 elections in Serang Regency in accordance with the planned target of 75% has become a concern for election organizers. To overcome this case, one of them is by involving the community as subjects in political activities and can utilize the role of the media as a means of increasing political participation. The purpose of this community service is to provide an understanding of the role of the media and political participation. While the method used is Participatory Action Research (PAR), which provides information through seminar activities and two-way question and answer discussions about the role and impact of the media and types of political participation. The results of these activities are that the community is less aware of the role of the media as a means to increase political participation, a source of knowledge information and as a means of criticism, suggestions and responses. Also, participation is not only as an object but also as a subject of change. On this basis, the government and other stakeholders need to develop a sustainable political education program to increase awareness of political participation and form social groups concerned with democracy.Kasus tidak tercapainya jumlah partisipasi Masyarakat pada Pemilihan Tahun 2020 di Kabupaten Serang sesuai dengan target yang direncanakan yakni 75%, menjadi peerhatian penyelenggara pemilu. Untuk mengatasi kasus tersebut salah satunya dengan pelibatan Masyarakat sebagai subyek dalam kegiatan politik serta dapat memanfaatkan peran media sebagai sarana meningkatkan partisipasi poltik. Adapun tujuan pengabdian kepada Masyarakat ini adalah memberikan pemahaman perihal peran media dan partisipasi politik. Sedangkan metode yang digunakan adalah Participatory Action Research (PAR), yakni memberikan informasi melalui kegiatan seminar serta diskusi tanya jawab secara dua arah tentang peran dan dampak media serta jenis partisipasi politik. Hasil dari kegiatan tersebut yakni Masyarakat kurang menyadari peran media sebagai sarana untuk meningkatkan partisipasi politik, sumber informasi pengetahuan serta sebagai sarana kritik, saran dan tanggapan. Pun partisipasi tidak hanya sebagai obyek namun juga sebagai subyek perubahan. Atas dasar demikian, pemerintah serta stakeholder lainnya perlu menyusun program Pendidikan politik secara berkelanjutan untuk meningkatkan kesadaran partisipasi politik serta membentuk kelompok sosial peduli demokrasi.